Analisis Investasi Sistem Informasi Akuntansi Terhadap Laporan Keuangan Peridoe 2022-2024 Pada PT ABC - Erisal 2226210010; Erisal Erisal; Anton Arisman (Universitas Multi Data Palembang, 2026)
: This study aims to analyze the effect of Accounting Information System (AIS) investment on the profit and loss performance of PT ABC during the 2022–2024 period. This research employs a quantitative approach using secondary data derived from the company’s financial statements. The analytical method applied is multiple linear regression, supported by classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The results indicate that AIS investment has a significant effect on the company’s profit and loss performance both partially and simultaneously. The coefficient of determination shows that AIS investment contributes substantially to explaining variations in the company’s profit and loss. These findings suggest that well-managed AIS investment can enhance financial performance in the long term. The results of this study are intended to serve as an evaluation and decision-making reference for the management of PT ABC regarding AIS investment, as well as a reference for academics and future researchers in the development of studies in the field of information systems and financial performance.